The Effect of Organic Manure and Days of Incorporation on the Growth and Yield of Lettuce (Lactuca sativa L.) Grown in Jos Plateau State. Nigeria - Madina, P; Iyough, D. D.; Michael, O. A; Ayoola, K (Discoveries in Agriculture and Food Sciences, 2023)
The experiment aimed to evaluate effect of organic manure on the growth and yield of lettuce (Lactuca sativa L.) grown in Jos Plateau State, Nigeria. The treatments used are organic manure source (Poultry dropping, Cow dung, goat manure, dung site and control) and time of inclusion (5, 10 and 15 days before transplanting) was adopted for the experiment. The experiment is laid in a randomized complete block design with three replications, with 12 plots in a block and 45 plots for the whole experiment. Data were collected from the following parameters, plant height, plant diameter, number of leaves, leaf area (LA), net assimilation rate (NAR), crop growth rate (CGR), fresh weight, and dry weight. All the study parameters of lettuce were significantly different (P<0.05) on both organic manure, days of inclusion and season. Poultry droppings produce plant height (25.73), plant diameter (8.42), number of leaves (32.02), leaf area index (16.75), net assimilation rate (4.67), crop growth rate (3.20), fresh weight (6.65 ha-1), and dry weight (4.23 ha-1) when compared with other sources of nutrient. Similarly maximum plant height (23.32), plant diameter (6.66), number of leaves (31.86), leaf area (15.19), net assimilation rate (3.32), crop growth rate (3.54), fresh weight (5.79 ha-1), and dry weight (4.00 ha-1) was recorded in lettuce plant treated with organic manure of 5 days of inclusion. On seasons, higher plant height (25.83), plant diameter (8.23), number of leaves (31.34), leaf area (15.32), net assimilation rate (4.00), crop growth rate (3.61), fresh weight (7.01 ha-1), and dry weight (5.99 ha-1) was obtained in 2021 as against 2020 season. Based on the results obtained, it can be recommended to lettuce farmers in the locality the use of poultry manure and 5 days of inclusion for optimum growth and yield of lettuce.